Implementasi Kebijakan Badan Layanan Umum Daerah: Studi Kasus RSUD dr. Soemarno Sosroatmodjo Tanjung Selor Kabupaten Bulungan - Iskandar, Iskandar; Mutiarin, Dyah (Universitas Muhammadiyah Yogyakarta, 2014)
The purpose of this study was to describe the policy implementation Public Service Agency (BLUD) in RSUD TanjungSelor. This study uses descriptive qualitative research with data collection through the data collection process impirismove from facts to theory building. Results of research policy implementation BLUD in RSUD Tanjung Selor show thatSPM has not run optimally meets standards and criteria set. BLUD running quite well due to the availability of medicalfacilities and hospital equipment, adequate human resource quality, health care procedures and treatment costs areaffordable. However, for many services still complained of patients considered less swift in responding to complaints.A common perception among the leaders of positive effect on the delivery of public health services, especially fromthe aspect of equity, and affordability of health care. In addition coordination and functional with health agencieshelped smooth implementation of accountable implementation. The ability of the police still lacked discipline officers,and less friendly. Comfort aspect of this facility is an extra burden on the patient. In the sense of this study indicate thatthe change of status into BLUDs at RSD Dr. Soemarno Sosroatmodjo Tanjung Selor Bulungan did not show a significantimpact on changes in the quality of service.